Implications of observed PBDE diffusion coefficients in low density polyethylene and silicone rubber. Issue 1 (18th December 2015) - Narváez Valderrama, Jhon F.; Baek, Kine; Molina, Francisco J.; Allan, Ian J.
Abstract : Significance of PBDE diffusivities in polymers for passive sampling and for the risk to biota when associated with microplastics. Abstract : A film-stacking technique was used to estimate diffusion coefficients of polybrominated diphenyl ethers (PBDEs) in low density polyethylene (LDPE) and silicone rubber. Substantially higher PBDE diffusion coefficients were observed for silicone rubber (AlteSil™) than for LDPE. A much steeper decrease in LDPE diffusion coefficients was found with increasing PBDE molecular weight than that for silicone rubber. From a passive sampling point-of-view, this means that for equivalent polymer–water partition coefficients for these two materials, the mass transfer resistance for these substances in the LDPE will be significantly higher than that for silicone rubber. Boundary layer control of the uptake process for silicone rubber can be expected for PBDEs. With a microplastic perspective, the low diffusion coefficients of PBDEs and in particular of decabromo diphenyl ether (BDE 209) in LDPE imply that the polymer diffusion coefficients for these plastic additives used as flame retardants need to be taken into account when considering the risk posed by microplastic particle ingestion by marine organisms.